COMPARISON OF POLICY FORMULATION ON CRIMINAL LEGAL SANCTIONS FOR NARCOTICS CRIMES IN INDONESIA AND MADAGASCAR - Andrianantenaina Fanirintsoa, Aime (Law Research Review Quarterly, 2024)
Narcotics crimes are on the verge of criminal acts that endanger the future of all Indonesian society and also damage education in Madagascar. This research aims to determine the policy for formulating criminal sanctions against drug users in Indonesia and Madagascar and to find out what aspects of punishment need to be prioritized for perpetrators of narcotics crimes on both sides. The author uses research methods with normative juridical legal research. The results of the research show that the effectiveness of law enforcement against criminal acts of abuse and illicit trafficking of narcotics in Indonesia and Madagascar is less effective. This is proven by the relatively short prison sentences handed down to perpetrators of narcotics abuse and distribution. Based on data collection from literature studies and case studies, perpetrators of drug abuse and illicit trafficking in Indonesia and Madagascar have increased from year to year. Efforts to various criminal sanctions objectives such as "Crime Reduction, Crime Suppression, Crime Prevention and Crime Control" have been carried out by the governments of Indonesia and Madagascar, both from the application of criminal sanctions and from the application of criminal sanctions. Law enforcement is already underway. Both by carrying out urine examination activities, counseling and seminars regarding the impacts and dangers of narcotics abuse as well as routine operations and special operations carried out by the police in both countries. This is proven by the reduction in criminal acts of abuse and distribution of narcotics originating from Indonesia and the majority of perpetrators coming from Madagascar.